Efeito da administração crônica de propranolol em alterações comportamentais e neuroquímicas no modelo de parkinsonismo induzido por reserpina - Tavares, Maria Micaelle Gomes (2025)
Parkinson's disease (PD) is the most prevalent multifactorial motor disorder in elderly individuals worldwide. The disease is characterized by the death of dopaminergic neurons in the substantia nigra pars compacta (SNpc) leading to motor symptoms. Studies show that noradrenergic dysfunction is associated with non-motor symptoms in the early stages of the disease. In addition, epidemiological studies show that chronic use of beta-adrenergic blockers increases the risk for PD. Thus, the objective of this study was to evaluate the effect of chronic administration of Propranolol on motor, non-motor and neurochemical alterations in a model of parkinsonism induced by reserpine. Thirty-nine male Wistar rats, 6 months of age (400 and 500 g), were used and submitted to chronic treatment with propranolol (PRO), doses of 10, 20 and 40 mg/kg, subcutaneously (s.c.), daily, for 60 days. In the last 30 days of the experiment, the animals were induced to parkinsonism with s.c. injections of reserpine (RES) 0.1 mg/kg, one injection every 48h, for a total of 15 injections. Thus, they were divided into the following groups: 1- Control (CTR, n = 7) that received the vehicle solutions; 2- Propranolol 40 (PRO40, n = 7) that received propranolol at a dose of 40 mg/kg; 3- Reserpine (RES, n = 5) that received reserpine; 4- Propranopol 10 and reserpine (PRO10+RES, n = 6); 5- Propranopol 20 and reserpine (PRO20+RES, n = 7); and 6-Propranopol 40 and reserpine (PRO40+RES, n = 7). Throughout the experiment, the animals were subjected to behavioral tests of catalepsy, open field (AC), oral movements (OM) and spontaneous alternation (SA). On the last day of the experiment, the animals were euthanized and the brains were collected and submitted to immunohistochemistry for Tyrosine Hydroxylase (TH+). CEUA no 6294030423. As results, in catalepsy, we observed that propranolol attenuated the motor damage induced by reserpine, since the RES group presented a longer time spent on the bar, compared to the PRO+RES groups (10, 20 and 40 mg/kg). In CA, propranolol did not affect the distance walked compared to the RES group, but the PRO10+RES group increased the number of no rearing compared to the RES group. In MO, PRO10+RES and PRO40+RES showed a lower number of vacuum chewing and the PRO10+RES group showed a shorter oral tremor time compared to the RES group. In AE, the PRO10+RES group showed a higher hit rate compared to the RES group. In immunohistochemistry, we observed that the PRO20+RES and PRO40+RES groups showed an increase in immunoreactivity for TH+ in the SNpc, as well as the PRO40+RES group in the Ventral Tegmental Area compared to RES. In the dorsal striatum, there was no difference between groups. Therefore, our data suggest that propranolol treatment attenuates motor, non-motor deficits and protects against the reduction of Th+ induced by the administration of reserpine. In addition, our data suggests that propranolol does not have a relationship of rich with PD, however, further studies are needed to understand the relationship between noradrenergic modulation and PD.